The Balinese Subak as World Cultural Heritage: In the Context of Tourism - Shinji Yamashita (Pusat Kajian Bali Universitas Udayana, 2013)
Abstract“Cultural Landscape of Bali Province: the Subak Systemas a Manifestation of the Tri Hita Karana Philosophy” wasinscribed in UNESCO’s World Heritage List in 2012. Thispaper discusses the Balinese subak as a world culturalheritage site in the context of cultural resources, culturalpolitics, and cultural tourism, comparing it with otherworld cultural heritage sites in East Asia. The paper alsoexamines subak and agriculture from the viewpoint ofvillage tourism, which has been developed in recent yearsas an alternative to mass tourism. In so doing, the paperaims to contribute to the discussion of complex culturaland agricultural processes in contemporary Bali. Thepaper concludes that making cultural heritage in the age ofglobalization is a dynamic process, involving local, nationaland global levels. What is important, then, is to createnew meanings in the cultural landscape for a sustainablefuture.